2017
DOI: 10.1111/jvim.14834
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Various Factors on Circulating 25(OH) Vitamin D Concentrations in Dogs with Cancer and Healthy Dogs

Abstract: BackgroundLow blood 25‐hydroxyvitamin D (25(OH)D) concentrations have been associated with cancer in dogs. Little research has examined what other factors may affect 25(OH)D concentrations.Objectives(1) To determine whether the presence of cancer (lymphoma, osteosarcoma, or mast cell tumor [MCT]) in dogs is associated with plasma 25(OH)D concentrations and (2) identify other factors related to plasma 25(OH)D concentrations in dogs.AnimalsDogs newly diagnosed with osteosarcoma (n = 21), lymphoma (n = 27), and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
36
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 46 publications
(102 reference statements)
3
36
3
Order By: Relevance
“…Weidner et al (2017) observed that dogs with lymphoma (n = 27), osteosarcoma (n = 21) and mastocytoma (n = 21) had lower serum 25(OH)D concentrations compared to a control group of healthy dogs. In this study, it was possible to collect samples of the foods consumed by the majority of dogs that participated in the experiment to analyse vitamin D levels.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Weidner et al (2017) observed that dogs with lymphoma (n = 27), osteosarcoma (n = 21) and mastocytoma (n = 21) had lower serum 25(OH)D concentrations compared to a control group of healthy dogs. In this study, it was possible to collect samples of the foods consumed by the majority of dogs that participated in the experiment to analyse vitamin D levels.…”
mentioning
confidence: 94%
“…The relationship of vitamin D and diseases has also been investigated in dogs and cats, and some studies found association between low vitamin D status and some types of cancer (Selting, Sharp, Ringold, Thamm, & Backus, 2016;Wakshlag et al, 2011;Weidner et al, 2017), congestive heart failure (Kraus et al, 2014;Osuga et al, 2015), gastrointestinal diseases (Allenspach, Rizzo, Jergens, & Chang, 2017;Gow et al, 2011;Lalor et al, 2014;Titmarsh, Gow, Kilpatrick, Cartwright, et al, 2015;Titmarsh, Gow, Kilpatrick, Sinclair, et al, 2015), acute pancreatitis (Kim et al, 2017), acute polyradiculoneuritis (Laws, Kathrani, Harcourt-Brown, Granger, & Rose, 2018), chronic kidney disease (Cortadellas, Fernandez del Palacio, Talavera, & Bayón, 2010;Galler et al, 2012;Gerber, Hässig, & Reusch, 2003;Gerber, Hauser, & Reusch, 2004;Parker, Harjes, et al, 2017) and infectious diseases (Lalor et al, 2012;Rodriguez-Cortes et al, 2017;Rosa, Schoeman, Berry, Mellanby, & Dvir, 2013;. Although these studies do not prove a cause-effect relationship, they provide a basis for future studies to investigate possible positive effects of vitamin D supplementation on improving health status and reducing the risk of developing diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that vitamin D deficiency is associated with skeletal and non-skeletal disease in companion animals [19][20][21][22][23][24][25][26][27][28][29] and reproductive outcomes in farm animals [30].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the prevalence of canine obesity and research demonstrating the occurrence of systemic inflammation in obese dogs, to our knowledge, the relationship between vitamin D status and obesity in dogs has not been investigated ( 27 29 ) . In a recently published study evaluating plasma 25(OH)D concentrations in sixty-nine dogs with cancer and twenty-three healthy control dogs, a significant relationship between body condition score (BCS) and vitamin D status was not found ( 30 ) . The majority of dogs in the study were in ideal body condition or overweight, and the number of obese subjects was not described ( 30 ) .…”
mentioning
confidence: 99%
“…In a recently published study evaluating plasma 25(OH)D concentrations in sixty-nine dogs with cancer and twenty-three healthy control dogs, a significant relationship between body condition score (BCS) and vitamin D status was not found ( 30 ) . The majority of dogs in the study were in ideal body condition or overweight, and the number of obese subjects was not described ( 30 ) . One goal of the present study was to assess the relationship between adiposity and vitamin D status (as indicated by serum 25-hydroxyvitamin D 3 (25(OH)D 3 ) and 24,25-dihydroxyvitamin D 3 (24,25(OH) 2 D 3 ) concentrations) in otherwise healthy adult dogs in ideal, overweight or obese body condition.…”
mentioning
confidence: 99%